The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1007/s00382-015-2610-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and diurnal variations of storm heights in the East Asia summer monsoon: storm height regimes and large-scale diurnal modulation

Abstract: variation of the storm height distribution, thereby providing unique differences in the rainfall amount, intensity, and the diurnal variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Owing to the Tropical Rainfall Measuring Mission (TRMM) satellite and the successive Global Precipitation Measurement (GPM) satellite, a variety of precipitation characteristics in early summer, including heavy precipitation, have been revealed throughout East Asia (Takayabu and Hikosaka 2009;Xu et al 2009;Xu 2013;Yokoyama et al 2014Yokoyama et al , 2017Park et al 2016). Based on three-dimensional observations of precipitation by the TRMM satellite-borne Precipitation Radar (PR), Yokoyama et al (2014) showed that precipitation characteristics drastically change in the meridional direction across the baiu front, which is detected as a boundary between the tropics and midlatitudes based on the largescale environment.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the Tropical Rainfall Measuring Mission (TRMM) satellite and the successive Global Precipitation Measurement (GPM) satellite, a variety of precipitation characteristics in early summer, including heavy precipitation, have been revealed throughout East Asia (Takayabu and Hikosaka 2009;Xu et al 2009;Xu 2013;Yokoyama et al 2014Yokoyama et al , 2017Park et al 2016). Based on three-dimensional observations of precipitation by the TRMM satellite-borne Precipitation Radar (PR), Yokoyama et al (2014) showed that precipitation characteristics drastically change in the meridional direction across the baiu front, which is detected as a boundary between the tropics and midlatitudes based on the largescale environment.…”
Section: Introductionmentioning
confidence: 99%